The rpoB gene of Mycobacterium tuberculosis. - Miller, L P (1994)
A portion of the Mycobacterium tuberculosis gene encoding the beta subunit of RNA polymerase (rpoB) was amplified by PCR using degenerate oligonucleotides and used as a hybridization probe to isolate plasmid clones carrying the entire rpoB gene of M. tuberculosis H37Rv, a virulent, rifampin-susceptible strain. Sequence analysis of a 5,084-bp SacI genomic DNA fragment revealed a 3,534-bp open reading frame encoding an 1,178-amino-acid protein with 57% identity with the Escherichia coli beta subunit. This SacI fragment also carried a portion of the rpoC gene located 43 bp downstream from the 3' end of the rpoB open reading frame; this organization is similar to that of the rpoBC operon of E. coli. The M. tuberculosis rpoB gene was cloned into the shuttle plasmid pMV261 and electroporated into the LR223 strain of Mycobacterium smegmatis, which is highly resistant to rifampin (MIC > 200 micrograms/ml). The resulting transformants were relatively rifampin susceptible (MIC = 50 micrograms/ml). Using PCR mutagenesis techniques, we introduced a specific rpoB point mutation (associated with clinical strains of rifampin-resistant M. tuberculosis) into the cloned M. tuberculosis rpoB gene and expressed this altered gene in the LR222 strain of M. smegmatis, which is susceptible to rifampin (MIC = 25 micrograms/ml). The resulting transformants were rifampin resistant (MIC = 200 micrograms/ml). The mutagenesis and expression strategy of the cloned M. tuberculosis rpoB gene that we have employed in this study will allow us to determine the rpoB mutations that are responsible for rifampin resistance in M. tuberculosis.